Comparação do efeito antinociceptivo do maropitant, antagonista nk-1, em diferentes doses, em cadelas submetidas à ovariohisterectomia - Andressa Karollini e Silva (2020)
Multimodal analgesia consists of the use of several drugs that have different mechanisms of action, aiming to promote adequate analgesia with a lower incidence of adverse effects. Maropitant is an antiemetic antagonist of NK-1 receptors linked to substance P, these receptors are located in the center of vomit and also in the nociceptive pathways, being identified in the viscera, spinal cord and brain. The present study aimed to compare the antinociceptive effect of maropitant in different doses, in bitches anesthetized with sevoflurane submitted to ovariohysterectomy by means of cardiorespiratory parameters, ETSEVO and body temperature, in addition to evaluate the analgesic requirement in the postoperative period using the Glasgow Pain Scale (ECDG). Forty-five adult female dogs, distributed in five groups of nine animals, weighing an average of 12.1 ± 4.2 kg were sedated with acepromazine (0.02 mg/kg, IM) and morphine (0.5 mg/kg, IM) for surgical preparation. After induction with propofol dose response (1 to 6 mg/kg IV) and maintenance of the anesthetic plan with sevoflurane, a bolus of maropitant (1 mg/kg) was administered intravenously, followed by continuous infusion of maropitant in increasing doses in four groups, they being G50 (50 mcg/kg/h), G75 (75 mcg/kg/h), G100 (100 mcg/kg/h) and G200 (200 mcg/kg/h) and a control group (n=9) that received the equivalent volume of CI in 0.9% NaCl. The cardiorespiratory parameters (HR, f, PAS / PAD / PAMinvasiva, SpO2, EtCO2), ETSEVO and rectal temperature were evaluated at seven different times, being preinduction (M0), post-induction (M1), surgical incision (M2 ), traction of the right ovarian pedicle (M3), traction of the left ovarian pedicle (M4), uterine traction (M5) and completion of skin suture (M6). If there was a 20% increase in HR and MAP values in relation to M0, analgesic rescue with fentanyl (1 mcg/kg, IV) was performed. Pain scores (ECDG) were assessed 1h, 2h, 4h and 6h after surgery and rescue with tramadol (5 mg/kg, SC) was administered in case of ECDG> 6. For data analysis, ANOVA was performed followed by the F test. Parametric measurements were compared using the Tukey test and non-parametric ones using the Kruskal-Wallis and SkillingsMack or Friedman tests with p <0.05. No significant difference was observed between analgesic protocols for cardiorespiratory variables and rectal temperature. As for ETSEVO, there was a statistical difference between the CG and the G50 (p = 0.04) and between the CG and the G100 (p = 0.03). In the assessment of postoperative pain by ECDG, no significant difference was observed between groups. It is concluded that the administration of maropitant in continuous infusion during the operation of bitches submitted to ovariohysterectomy demonstrated efficacy in reducing the average anesthetic requirement of sevoflurane in groups G50 and G100, however, it was not sufficient to suppress autonomic responses to somatic and visceral nociceptive stimuli. and showed no evident effect on the scores of the postoperative pain assessment by ECDG.